Niveles de compost de rastrojos de cosechas del cultivo de plátano y su influencia en Cucumis sativus L. variedad pepino regional, región Loreto.2022 - Vela Rengifo, Arnold (2023)
The paper concerning the levels of compost of stubble of the banana crop, in Cucumis sativus L. variety cucumber regional, Loreto region. 2022, was installed in the "Fundo Zungarococha ,of the property of Agronomy of the UNAP, presenting a general objective of Fix the influence of the levels of compost of stubble of crops of the banana field in Cucumis sativus L. variety cucumber regional,, having as criterion the management of the Statistical Design of the DBCA, whose values obtained led to the following: The tillage of cucumber regional variety responds very well to the placement of compost of banana crop residues; the T4 of greater amount of fertilization presented the best results in the crop; The best fruit utility was obtained in the portion of 60 t of compost/ha with 27 t/ha; likewise, it presented the best monetary return with a profit of S / 39,051.00.